2008
DOI: 10.1007/s12105-007-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Epstein–Barr Virus (EBV) by In situ Hybridization as Definitive Diagnosis of Hairy Leukoplakia

Abstract: Histopathological findings in cases of hairy leukoplakia (HL) are not exclusive to this lesion. A total of 36 tissue samples from patients previously diagnosed with HL based solely on morphological aspects were used in this study. Our purpose was to confirm the presence of EpsteinBarr virus (EBV) in these tissue samples by in situ hybridization (ISH), and to compare the detection of EBV with specific histopathological findings observed in each case. Among the 36 specimens, 80.55% were EBV positive, confirming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 33 publications
1
34
0
6
Order By: Relevance
“…A comparative study between sialometry techniques and minor salivary gland biopsy in patients with Sjogren's syndrome showed no difference in sensitivity between both procedures and the authors concluded that the positivity of both tests increases the specificity for Sjögren's syndrome (95%) than when they are considered in isolation. In recent years research has focused on less invasive diagnostic methods in order to cause a minor annoyance in patients [19][20][21].…”
Section: Development Physiological Changes In Salivarymentioning
confidence: 99%
See 1 more Smart Citation
“…A comparative study between sialometry techniques and minor salivary gland biopsy in patients with Sjogren's syndrome showed no difference in sensitivity between both procedures and the authors concluded that the positivity of both tests increases the specificity for Sjögren's syndrome (95%) than when they are considered in isolation. In recent years research has focused on less invasive diagnostic methods in order to cause a minor annoyance in patients [19][20][21].…”
Section: Development Physiological Changes In Salivarymentioning
confidence: 99%
“…To validate the cytology as a complementary exam, for diagnosis of Hairy leukoplakia using in situ techniques (hybridization) for the detection in oral mucosa. Thus, diagnostic studies involving hairy leukoplakia orally in situ hybridization for EBV detection based cytology via ThinPrep test Pap shown that cytology EBV-associated hybridization is simple, efficient and non-invasive tool as efficient as biopsies [19].…”
Section: Saliva Testsmentioning
confidence: 99%
“…5,6 As these histologic features are not exclusive to OHL, a definitive diagnosis relies on the detection of EBV in the lesional tissue. 6 …”
Section: Histologic Appearancementioning
confidence: 99%
“…5,6 However, ISH is the most widely used method and is considered the "gold standard" for the detection of the DNA or RNA of EBV in tissue sections. 7,8 Pathogenesis…”
Section: Statement Of Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation